The Environment Teacher Performance on Leadership Style Work Motivation, and Non-Physical Work - Rafli Dwi Putra; Kurbandi Satpatmantyo BR (Vifada Journal of Education, 2024)
This study was conducted at SDN Aren Jaya 18, involving 36 teachers as respondents. The aim of this research is to explore the influence of leadership style, work motivation, and non-physical work environment on teacher performance, both partially and simultaneously. The method used in this research is a quantitative approach. The results show that leadership style partially has a significant impact on performance, with a t-value of 1.816 > t-table 1.693 and a significance value (sig) less than 0.05. Work motivation also partially has a significant impact on performance, with a t-value of 1.880 > t-table 1.693 and a significance value (sig) less than 0.05. The non-physical work environment partially has a significant impact on performance, with a t-value of 1.747 > t-table 1.693 and a significance value (sig) less than 0.05. Simultaneously, leadership style, work motivation, and the non-physical work environment significantly influence teacher performance. The combined influence of these three variables on performance reaches 68%, while the remaining 32% is influenced by other variables not examined in this study. The theoretical implications of these findings suggest that effective leadership style, high work motivation, and a conducive non-physical work environment are important factors in enhancing teacher performance. Meanwhile, the practical implications are that the school and related parties can use these findings as a basis for designing and implementing programs for leadership development, motivation, and improving the work environment to enhance teacher performance.